Analisis Faktor-Faktor Yang Mempengaruhi Niat Menonton Film Bioskop: Studi Kasus Kota Batam - Hendrawan, Hendrawan (GEMA EKONOMI, 2023)
Watching movies in the cinema has often been done by the people in the city. there are many cinema places that people visit to watch movies. This study aims to determine the influence of Film Quality, Brand Image, Attractiveness, Word of mouth on the intention of watching movies in batam city. In quantitative research, 400 respondents will be taken and 30 respondents for qualitative research. In this study, disproportionate random sampling and multiple regression methods were used. The application used for data processing is IBM SPSS statistics 24. From the test results on the hypothesis that states that there is a significant influence on the results obtained by the variables Film Quality, Brand Imagery, Attractiveness, and Word of mouth have a positive effect on viewing interest in the batam community.